The most wonderful crime of the year eaudiobook A novel. - Carter, Ally (HarperAudio, 2024)
""Full of tongue-in-cheek humor, excellent dialogue, and fantastic characters, this expertly crafted story from Carter (The Blonde Identity) is a heart-melting rivals-to-lovers romance combined with a delightful locked-room mystery."" — Library Journal (starred review) Knives Out gets a holiday rom-com twist in this rivals-to-lovers romance-mystery from New York Times bestselling author Ally Carter. The bridge is out. The phones are down. And the most famous mystery writer in the world just disappeared out of a locked room two days before Christmas. Meet Maggie Chase and Ethan Wyatt: She's the new Queen of the Cozy Mystery. He's Mr. Big-time Thriller Guy. She hates his guts. He thinks her name is Marcie (no matter how many times she's told him otherwise.) But when they both accept a cryptic invitation to attend a Christmas house party at the English estate of a reclusive fan, neither is expecting their host to be the most powerful author in the world: Eleanor Ashley, the Duchess of Death herself. That night, the weather turns, and the next morning Eleanor is gone. She vanished from a locked room, and Maggie has to wonder: Is Eleanor in danger? Or is it all some kind of test? Is Ethan the competition? Or is he the only person in that snowbound mansion she can trust? As the snow gets deeper and the stakes get higher, every clue will bring Maggie and Ethan closer to the truth—and each other. Because, this Christmas, these two rivals are going to have to become allies (and maybe more) if they have any hope of saving Eleanor. Assuming they don't kill each other first. The laugh out loud holiday ""romystery"" that you've been waiting for!